(untitled) (Social Science Review, 2023)
The intensification of Sino-Japanese antipathy in Southeast Asia through competitive vaccine diplomacy is a significant development, given the region’s geopolitical importance to both rivals. Despite this, there has been a lack of research on the geopolitical dimensions of Japan and China’s vaccine contestation in Southeast Asia. Thereby, this study aims to examine the influence of geopolitics on Sino-Japanese competitive vaccine diplomacy in the region, using online-based secondary data. The study argues that both China and Japan have donated millions of vaccine shots to Southeast Asian countries to reinforce their relationships with the region, driven by their respective geopolitical interests. Overall, this research contributes to a deeper understanding of the interplay between geopolitics and vaccine diplomacy in Southeast Asia. Social Science Review, Vol. 39(2), June 2022 [Special Issue] Page 99-119